Tardive dystonia associated with olanzapine therapy - (:unkn) unknown (SPRINGER-VERLAG, 2001)
A 21-year-old man with the diagnosis of paranoid schizophrenia was admitted to our clinic with cervical dystonia developing at the end of the first year of olanzapine therapy. The present case suggests that tardive dystonia in this patient is most likely associated with olanzapine administration as this is the main antipsychotic he received. Regarding the few case reports of olanzapine-associated tardive syndromes, patients taking olanzapine should be carefully screened for the appearance of tardive movements.
Keywords: tardive dystonia; olanzapine; atypical; neuroleptic; DYSKINESIA